The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/aenm.202201383
|View full text |Cite
|
Sign up to set email alerts
|

Water Droplet‐Based Nanogenerators

Abstract: Water is one of the most sustainable resources in the world, offering an abundance of hydro energy. Getting a large amount of electricity through conventional water energy harvesting is expensive, with complex mechanisms and bulky installation systems. In the case of the small amount of energy for some portable electronic devices and sensor systems, water droplet harvesting as a sustainable energy resource has become a forward‐looking step to meet the future demand for green energy. The ultimate demand for gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 158 publications
0
22
0
Order By: Relevance
“…In addition to the small number of ingredients in sweat, recent research suggests that droplets may also be used to generate electricity. 160 Therefore, water, which is the most abundant component of sweat, can also be used for power supply. In 2022, Xingcan Huang et al 161 used the redox reaction of sweat with magnesium and combined near-field communication (NFC) technology to prepare sweat-activated batteries embedded in textiles, as shown in Figure 11d.…”
Section: Power Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the small number of ingredients in sweat, recent research suggests that droplets may also be used to generate electricity. 160 Therefore, water, which is the most abundant component of sweat, can also be used for power supply. In 2022, Xingcan Huang et al 161 used the redox reaction of sweat with magnesium and combined near-field communication (NFC) technology to prepare sweat-activated batteries embedded in textiles, as shown in Figure 11d.…”
Section: Power Supplymentioning
confidence: 99%
“…Because of the lower content of reactants in sweat, the resulting energy density and open-circuit voltage are 0.26–252 μW cm –2 and 0.31–1.08 V, respectively. In addition to the small number of ingredients in sweat, recent research suggests that droplets may also be used to generate electricity . Therefore, water, which is the most abundant component of sweat, can also be used for power supply.…”
Section: Applicationsmentioning
confidence: 99%
“…[20] Subsequently, this environmentally friendly, efficient and easy-to-operate method quickly attracted the attention of scholars worldwide, opening a new chapter in the research of collecting renewable clean energy from water. [21][22][23][24][25][26] The SL-TENGs cleverly combine solid-liquid interface CE and electrostatic induction, and as micro-nano energy harvesters, show significant advantages and prospects in energy harvesting and utilization from water in the forms of water resources such as droplets, waves, and flows, and others. So far, research on SL-TENGs has been developed for nearly a decade (Figure 1), and their applications involve blue energy harvesting, [27] physical sensors, [28] chemical sensors, [29] biomedicine, [30] underwater wireless communication, [31] and many other fields.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] TENG can be as self-powered sensors to output electric signals according to external stimulus with advantages of simple structure and low cost. [7][8][9] So far, TENG has been employed in different contacting interfaces, such as solid-solid interface, liquid-solid interface, liquid-liquid interface and etc. [10][11][12] For liquid-solid TENG DOI: 10.1002/adfm.202302147 (LS-TENG), recent studies have demonstrated that LS-TENG was used as selfpowered sensors in the field of droplet motion monitoring, [13] lubricating oil condition monitoring [14] and ship draft detecting.…”
Section: Introductionmentioning
confidence: 99%